Acupuncture Improves Sleep Conditions of Minipigs Representing Diurnal Animals through an Anatomically Similar Point to the Acupoint (GV20) Effective for Humans. (16th February 2012) - Takeishi, Ka-ichiro; Horiuchi, Masahisa; Kawaguchi, Hiroaki; Deguchi, Yoshiki; Izumi, Hiroyuki; Arimura, Emi; Kuchiiwa, Satoshi; Tanimoto, Akihide; Takeuchi, Toru
Abstract : Acupuncture, an alternative medicine, has been widely applied for people with sleep disturbances; therefore, the effects should be evaluated objectively. Micro-minipigs (MMPigs), the smallest miniature pigs for animal experiments, were used. Acupuncture was performed at two different points: Dafengmen is located on the head and is an anatomically similar point to human-Baihui (GV20), an effective acupoint for sleep disturbances in humans; pig-Baihui is on the back. The procedure was performed as follows: shallow, within 5 mm depth for several seconds; deep, 10–20 mm depth for 20 min. The sleep conditions were evaluated by actigraph, and the amount of catecholamine in pooled urine after acupuncture treatment. MMPigs with deep acupuncture at Dafengmen showed significantly efficient values on actigraph and catecholamine analysis as compared with untreated MMPigs. The effective acupoint for sleep conditions in the porcine model is at an anatomically similar point to humans, rather than the point determined by traditional Chinese medicine.